Omissão de macronutrientes na nutrição e no crescimento da cana-de-açúcar cultivada em solução nutritiva - Do Vale, Diego W.; De M. Prado, Renato [UNESP]; Avalhães, Cíntia C.; Hojo, Ronaldo H. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2011)
Nutrients deficiency may limit the nutrition, growth and production of sugarcane. In this context, the objective of this work was to evaluate the growth, dry matter production, nutrient content and nutrients accumulation in sugarcane plants grown in nutritious solution, submitted to macronutrients omission, and to describe the visual symptoms of such omission. The experiment was carried out at the School of Agrarian and Veterinarian Sciences - Jaboticabal Campus, São Paulo, Brazil, with seven treatments (complete and with the omission of N, P, K, Ca, Mg and S), arranged in a completely randomized design, with three replications. Eleven weeks after the transplant to the nutrient solutions, the tiller number the fully developed leaves number, the height, the tillers diameter, the plant dry matter and the shoot and root macronutrient content of sugarcane were evaluated. N and P were the nutrients that limited the growth of sugarcane plants the most, with reductions of 91 and 57 %, respectively. However, regarding the root growth, the omission of N and Ca resulted in the greatest limitations, reducing the root growth in 83 and 48%, respectively.
Macronutrients omission in the nutrition and growth of sugarcane grown in nutritious solution
Keywords: Nutrient solution; Nutritional disorder; Saccharum spp; Saccharum